1994
DOI: 10.1007/bf02048158
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of metastatic lymph nodes in colorectal cancer by the modified clearing method

Abstract: In the TNM classification, there was no significant difference between colon and rectal cancer except pT1 with rectal cancer. In the lower rectal cancer within 6 cm from the anal verge or beyond pT3, there is a high risk of lateral metastasis, and lateral lymph node dissection or radiation therapy should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 12 publications
2
89
2
6
Order By: Relevance
“…All the lymph nodes draining the tumour-area are located within the mesocolon, mainly along the large vessels as they run centrally [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…All the lymph nodes draining the tumour-area are located within the mesocolon, mainly along the large vessels as they run centrally [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The incidence of lateral cancer spread in patients with lower rectal cancer has been reported as 10% to 25%. 6,8 Further, occult metastases are present in approximately 4% of patients who, based on conventional histologic examination, are negative for lateral node involvement. 9 It may safely be said that there have never been any commonly accepted treatments for patients with such disease.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that this is a safe and feasible technique with at least the same morbidity and mortality as the "so called" standard technique. The concept of CME with CVL consists of creating an intact specimen encompassing the primary neoplasia along with all the potential pathways of tumor spread through central ligation of the main artery at its origin [9,10]. CME with CVL consists of two main components: the preservation of intact fasciae of the mesocolon between which relevant lymph nodes are contained in association with ligation of the blood vessels that supply the tumor colon site at their origin: at the level of the superior mesenteric vein for right sided neoplasms and at the level of their origin in the inferior mesenteric artery for left sided neoplasm [11].…”
Section: The Concept Of Complete Mesocolic Excisionmentioning
confidence: 99%